Hukum Pengobatan menurut Islam dan Sains - Azzahro, Salsa Billa Dwi (Maliki Interdisciplinary Journal, 2024)
Medical law is the intersection of religious values, scientific knowledge and state regulation. Islam, as the majority religion in many countries, has a comprehensive view of health and medicine that emphasizes the importance of maintaining a healthy body as a gift from God. Islamic principles in medicine include seeking treatment, avoiding things that harm health, and believing that healing comes from God. On the other hand, the development of science has given birth to a variety of increasingly sophisticated methods of modern medicine. Science offers empirical evidence of the effectiveness of various therapies and treatments. The confluence of these two perspectives often raises ethical and legal dilemmas. For example, the use of advanced reproductive technologies, the use of vaccines, or alternative medicine. In this context, it is important to strike a balance between religious values, scientific evidence and societal interests. This article will take an in-depth look at the laws of medicine from the perspectives of Islam and science.